2015
DOI: 10.1115/1.4030011
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Carotid Artery Under Steady-State and Pulsatile Blood Flow: A Fluid–Structure Interaction Study

Abstract: It has been shown that arteries may buckle into tortuous shapes under lumen pressure, which in turn could alter blood flow. However, the mechanisms of artery instability under pulsatile flow have not been fully understood. The objective of this study was to simulate the buckling and post-buckling behaviors of the carotid artery under pulsatile flow using a fully coupled fluid-structure interaction (FSI) method. The artery wall was modeled as a nonlinear material with a two-fiber strain-energy function. FSI sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…The decrease in collagen IV in the buckled arteries could be due to both the increases in lumen shear stress and wall stresses, 5,15,28 though we could not distinguish which stress component led to the difference between the inner and outer curves. Shear stress was found higher at the inner curve of buckled arteries, 27 which is most likely the mechanism that led to increased MMP-2 expression, as suggested by Sho et al 36 Buckling-induced changes in hemodynamics, mechanical stress, endothelial cell function, and ECM remodeling could be a possible mechanism for the high occurrence of atherosclerosis in tortuous carotid arteries. 8,29 …”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The decrease in collagen IV in the buckled arteries could be due to both the increases in lumen shear stress and wall stresses, 5,15,28 though we could not distinguish which stress component led to the difference between the inner and outer curves. Shear stress was found higher at the inner curve of buckled arteries, 27 which is most likely the mechanism that led to increased MMP-2 expression, as suggested by Sho et al 36 Buckling-induced changes in hemodynamics, mechanical stress, endothelial cell function, and ECM remodeling could be a possible mechanism for the high occurrence of atherosclerosis in tortuous carotid arteries. 8,29 …”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, flow and shear stress of different conditions (laminar and perturbed, unidirectional/oscillatory) can differentially regulate eNOS expression. 37,44 Our previous computational analysis demonstrated that flow in the buckled arteries was laminar and unidirectional, 27 similar as in straight control vessels. However, the shear stress magnitude and its spatial distribution are different in buckled and straight vessels.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Computational methods, in which equations are coupled governing the flow and the elastic walls are maturing. [15][16][17][18] There is a lack of experimental data in compliant arterial systems to validate the numerical predictions with only a few publications available. [19][20][21] Early work with healthy arterial geometries by Perktold et al 22 numerically investigated the effect of compliance on a geometry representing the human common carotid artery (CCA) bifurcation experiencing a physiologically realistic waveform making observations of both the WSS and vessel compliance.…”
mentioning
confidence: 99%